Thrombolytic therapy in patients with submassive pulmonary embolism: A systematic review - Kittinaradorn, Donya; Tangnuntachai, Nichthida; Wongjarupong, Nicha; Longchit, Duangthip; Atipookanok, Songphoom; Boondarikpornpant, Thosaporn; Nopmaneepaisarn, Titaporn; Papassornsiri, Thipyada; Soopanit, Thanion; Tantirungsi, Tanaboon; Supakmontri, Thanapat; Rattanaphong, Tanavadee; et al. (Chulalongkorn Medical Journal, 2023)
Background : The use of thrombolytic therapy in patients with submassive pulmonary embolism (PE) is still controversial. Objective : To evaluate the role of thrombolytic therapy in patients with submassive PE. Design Systematic review. Setting : Faculty of Medicine, Chulalongkorn University. Methods : We performed a literature search using Pubmed, Scopus, scientific abstracts from meetings, and bibliographies of retrieved articles. Only randomized control trials were included in this systematic review. Result : Three randomized control trials were identified. All these studies excluded patients with high risk of bleeding. The evidence from randomized control trials identified in this systematic review suggested that thrombolytic therapy in addition to heparin may provide a long-term mortality benefit, prevent clinical deterioration, and preserve right ventricular function with a slightly increased risk of minor bleeding in patients with submassive PE. The benefits of thrombolytic therapy were most obvious in a randomized control trial that enrolled patients within 6 hours after the onset of the symptoms. Conclusion : Thrombolytic therapy may be considered in patients with submassive PE who have low risk of bleeding complications and present early after the onset of the symptoms.